2014
DOI: 10.1097/ppo.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Survival Disparities in Non–Small Cell Lung Cancer by Race, Ethnicity, and Socioeconomic Status

Abstract: We found strong evidence for racial and socioeconomic disparities in Floridian NSCLC survival. Asians had improved survival compared with whites, a novel finding. Our findings confirmed that patients living in lower socioeconomic neighborhoods have worse outcomes than their wealthier neighborhood counterparts. Finally, we found an association between some modifiable factors/comorbidities and worse survival. Clinicians may be able to use this information to improve patients' likelihood of better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
81
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 23 publications
11
81
4
1
Order By: Relevance
“…In our study, we have also demonstrated that race is significantly associated with the extent of lymph node evaluation, which is consistent with other studies that have demonstrated racial disparities of care in the treatment of lung cancer [34, 35]. We have additionally demonstrated that treatment at a high-volume center as well as at a center with an academic association are both associated with the extent of lymph node evaluation, which also corresponds to other studies that have demonstrated a survival benefit in lung cancer resection by treatment at academic and high volume centers [36].…”
Section: 0 Discussionsupporting
confidence: 92%
“…In our study, we have also demonstrated that race is significantly associated with the extent of lymph node evaluation, which is consistent with other studies that have demonstrated racial disparities of care in the treatment of lung cancer [34, 35]. We have additionally demonstrated that treatment at a high-volume center as well as at a center with an academic association are both associated with the extent of lymph node evaluation, which also corresponds to other studies that have demonstrated a survival benefit in lung cancer resection by treatment at academic and high volume centers [36].…”
Section: 0 Discussionsupporting
confidence: 92%
“…Patients treated at academic centers were more likely to be Black (African American), Asian, or Hispanic. Asians with NSCLC have improved OS due to difference in disease biology such as increased prevalence of epidermal growth factor receptor (EGFR) mutation . A California Cancer Registry study showed improved NSCLC‐specific mortality among foreign‐born Hispanics compared to non‐Hispanic Whites and Hispanics born in United States .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond racial disparities, socioeconomic status (SES), as measured by income level or degree of education, also recently was associated with multiple poor health outcomes, including diabetes, cardiovascular disease, and cancer . Population cohort studies in lung and esophageal cancers have suggested that one's social environment, as defined by area‐based socioeconomic measures, may be associated with worse survival outcomes, possibly due to poor screening or receipt of therapy . Such class disparities ultimately may mitigate improvements in outcomes, and warrant further evaluation to identify root causes of poor health and inequalities.…”
Section: Introductionmentioning
confidence: 99%